2015
DOI: 10.3389/fpsyg.2015.00819
|View full text |Cite
|
Sign up to set email alerts
|

How our body influences our perception of the world

Abstract: Incorporating the fact that the senses are embodied is necessary for an organism to interpret sensory information. Before a unified perception of the world can be formed, sensory signals must be processed with reference to body representation. The various attributes of the body such as shape, proportion, posture, and movement can be both derived from the various sensory systems and can affect perception of the world (including the body itself). In this review we examine the relationships between sensory and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 94 publications
(111 reference statements)
2
38
0
Order By: Relevance
“…We can also hypothesize that perspective-taking is affected by other characteristics of the body such as morphology, flexibility, and body size. Such a role of the body is in line with the view that multisensory external information is integrated with information concerning the body state for perception (for a review, see Harris et al., 2015 ).…”
supporting
confidence: 60%
“…We can also hypothesize that perspective-taking is affected by other characteristics of the body such as morphology, flexibility, and body size. Such a role of the body is in line with the view that multisensory external information is integrated with information concerning the body state for perception (for a review, see Harris et al., 2015 ).…”
supporting
confidence: 60%
“…Previous studies on healthy adult subjects showed that gravitational vestibular signals can modulate orientation threshold suggesting that some orientation mechanisms are linked to vestibular coordinates ( Harris et al., 2015 , Lacquaniti et al., 2015 , Mikellidou et al., 2015 ). Altering gravitational and vestibular cues, by asking the subjects to perform the task while lying on a bed or with their head tilted, did not change the results.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a further support for the special relationship that the front and back of the body have with each other. The representations of the front and back of the body may be mapped together by the brain (Parsons and Shimojo, 1987;D' Amour and Harris, 2014;Harris et al, 2015;Hoover and Harris, 2015;Tamè et al, 2016). Thus, any distortion of one would be reflected in a comparable distortion of the other (see Figure 3).…”
Section: Front and Back Viewmentioning
confidence: 99%
“…We use our body to present ourselves and to perceive and interact in the world. Knowledge about body posture, position, size, and structure are required to interpret and react to sensory information that is constantly being received and that may be coded relative to the body (Kopinska and Harris, 2003;Harris et al, 2015). Processing sensations and generating actions requires the brain to accurately map and represent the body and the body-in-space.…”
Section: Introductionmentioning
confidence: 99%